Premenstrual Syndrome and Childbirth Fear Prior to Pregnancy in Young Women: An Association and Cross-Sectional Study - Ataman,Hacer (2022)
SUMMARY OBJECTIVE: The aim of the study was to determine the association between premenstrual syndrome and the childbirth fear prior to pregnancy. METHODS: This was an association and cross-sectional study conducted on 327 university students. Data were collected using “Participant Information Form,” “Premenstrual Syndrome Scale,” and “Childbirth Fear-Prior to Pregnancy Scale.” RESULTS: It was found that the childbirth fear had increased in students with premenstrual syndrome. The Women Childbirth Fear-Prior to Pregnancy Scale score was statistically significantly higher among students who preferred caesarean section than those who preferred vaginal delivery. There was a weak, positive, and statistically significant correlation between the students’ depressive sensation, anxiety, fatigue, nervousness, depressive thoughts, pain, appetite changes, sleep pattern changes, and bloating subscales of Premenstrual Syndrome Scale and Women Childbirth Fear-Prior to Pregnancy Scale. CONCLUSION: The score of the Women Childbirth Fear-Prior to Pregnancy Scale increases with an increase in the score of the Premenstrual Syndrome subscale. It should be evaluated whether or not women experiencing premenstrual syndrome have the childbirth fear prior to pregnancy.